Crosstalk of RNA methylation writers defines tumor microenvironment and alisertib resistance in breast cancer - Zhang, Xiaoqiang; Shen, Li; Zhu, Yanhui; Zhai, Changyuan; Zeng, Hanling; Liu, Xiaoan; Tao, Jing (Frontiers in Endocrinology, 2023)
Background: The five major RNA methylation modifications (m6A, m1A, m6Am, m5C and m7G) exert biological roles in tumorigenicity and immune response, mediated mainly by “writer” enzymes. Here, the prognostic values of the “writer” enzymes and the TCP1 role in drug resistance in breast cancer (BC) were explored for further therapeutic strategies. Methods: We comprehensively characterized clinical, molecular and genetic features of subtypes by consensus clustering. RNA methylation modification “Writers” and related genes_risk (RMW_risk) model for BC was constructed via machine learning approach. Moreover, a systematical analysis for characteristics of tumor microenvironment (TME), alisertib sensitivity and immunotherapy response was performed. A series of experiments in vitro were carried out to assess the association of TCP1 with drug resistance. Results: One “writer” (RBM15B) and two related genes (TCP1 and ANKRD36) were identified for prognostic model construction, validated by GSE1456, GSE7390, GSE20685 cohorts and our follow-up data. Based on the patterns of the genes related with prognosis, patients were classified into RMW_risk-high and -low subtypes. Lower RMW_Score was associated with better overall survival, the infiltration of immune cells such as memory B cell. Further analysis revealed that RMW_Score presented potential values in predicting drug sensitivity and response for chemo- and immunotherapy. In addition, TCP1 was confirmed to promote BC alisertib-resistant cell proliferation and migration in vitro. Conclusion: RMW_Score could function as a robust biomarker for predicting BC patient survival and therapeutic benefits. This research revealed a potential TCP1 role regarding alisertib resistance in BC, providing new sights into more effective therapeutic plans.